Ambiguity, Household and the Global Intimate in the Work of Henri Lefebvre - Shields, Rob (ACME, 2025)
Households are central to Henri Lefebvre’s 1940s-1980s critiques of everyday life. They are the first spaces of everyday modernity that he analyses and include an extended sociology of women’s contradictory roles in consumption and nurture. Households perpetuate archaic, patriarchal forms and are incompletely colonized by media and consumerism. On this basis, Lefebvre champions peasant households as repositories of alternative potential which could form the basis for a different socioeconomic order than capitalism. Feminist analysis of ‘the global intimate’ has seized on this promise but develop beyond Lefebvre’s heterosexist and romanticized view of post-World War II women as ambiguous, oppressed and deluded. This paper mines Lefebvre’s key texts for his treatment of heterosexual cis-women and men, violence, intimacy, patriarchy, feminism and gender. These dimensions of the household give a more precise understanding of Lefebvre’s romanticization of the patriarchal peasant household and community. He is a transitional figure from the Marxist tradition who prefigures feminist analyses of the global intimate. However, households hold promise as a ‘margin-within:’ an enclaved, nested, alternate spatialisation within the dominant order of social space. The everyday household emerges as a crucible and social form of differences and contradictions that could be extended into a ‘differential space’ that supports maximal diversity and opportunity with minimal organisation or regression to more oppressive intergenerational, kin and gender relations.